2016
DOI: 10.18632/oncotarget.7463
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive guidance molecule B inhibits metastasis and is associated with decreased mortality in non-small cell lung cancer

Abstract: Repulsive guidance molecules (RGMs) are co-receptors of bone morphogenetic proteins (BMPs) and programmed death ligand 2 (PD-L2), and might be involved in lung and other cancers. We evaluated repulsive guidance molecule B (RGMB) expression in 165 non-small cell lung cancer (NSCLC) tumors and 22 normal lung tissue samples, and validated the results in an independent series of 131 samples. RGMB was downregulated in NSCLC (P ≤ 0.001), possibly through promoter hypermethylation. Reduced RGMB expression was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…RGMb, a secondary receptor for PD-L2 18 , is a member of the repulsive guidance molecule (RGM) family that includes RGMa, RGMb, and RGMc 37 , and is expressed in the nervous system, macrophages, and other cells of the immune system 37 , 38 . Moreover, RGMb is also reported to be expressed in some tumors and has varying roles 39 41 . Previous studies show that RGMb is associated with tumorigenesis, immunoregulation, and cell-to-cell adhesion, and has an important role in the RGMb-neogenin-RhoA signaling pathway 19 , 42 45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGMb, a secondary receptor for PD-L2 18 , is a member of the repulsive guidance molecule (RGM) family that includes RGMa, RGMb, and RGMc 37 , and is expressed in the nervous system, macrophages, and other cells of the immune system 37 , 38 . Moreover, RGMb is also reported to be expressed in some tumors and has varying roles 39 41 . Previous studies show that RGMb is associated with tumorigenesis, immunoregulation, and cell-to-cell adhesion, and has an important role in the RGMb-neogenin-RhoA signaling pathway 19 , 42 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown the expression and interaction of RGMb/neogenin, RGMb/BMPs, or neogenin/BMPs, and most of the researches on RGMb/neogenin mainly focus on the nervous system 19 21 , 46 , 47 . RGMb is also reported to be expressed in some tumors such as breast cancer, colorectal cancer, and lung cancer, and has varying roles; 39 41 abnormal expression of neogenin has been found in pancreatic carcinoma, colon cancer, esophageal squamous cell carcinoma, gliomas, and breast cancer; 50 BMP and its receptors are also implicated with many cancers 22 . However, the systematic study for BBRN expression in tumor is rare.…”
Section: Discussionmentioning
confidence: 99%
“…; Li et al. ; Muller et al. ), most publications to date have focused on experimental model systems (Matsunaga et al.…”
Section: Discussionmentioning
confidence: 99%
“…ID1 inhibits the activation of E12/E47. It is predicted that ID1 dependent pancreatic cancers could be sensitive to specific ID1 small-molecule inhibitors [ 153 ]. The potential benefit of gefitinib in suppressing ID1 in K-Ras mutant NSCLC also warrants investigation.…”
Section: Transforming Growth Factor-β Signaling In K-ras Mutationmentioning
confidence: 99%